2016
DOI: 10.1162/neco_a_00890
|View full text |Cite
|
Sign up to set email alerts
|

Neural Quadratic Discriminant Analysis: Nonlinear Decoding with V1-Like Computation

Abstract: Linear-nonlinear (LN) models and their extensions have proven successful in describing transformations from stimuli to spiking responses of neurons in early stages of sensory hierarchies. Neural responses at later stages are highly nonlinear and have generally been better characterized in terms of their decoding performance on prespecified tasks. Here we develop a biologically plausible decoding model for classification tasks, that we refer to as neural quadratic discriminant analysis (nQDA). Specifically, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…One question of interest is the degree to which the target match versus distractor classification can be made with a linear decision boundary (or equivalently a linear decoder) applied to the IT neural data, as opposed to requiring a nonlinear decoding scheme. In a previous study, we assessed the format of IT target match information in the context of the classic DMS task design [ 11 , 19 ] and found that while a large component was linear, a considerable nonlinear (quadratic) component existed as well.…”
Section: Resultsmentioning
confidence: 99%
“…One question of interest is the degree to which the target match versus distractor classification can be made with a linear decision boundary (or equivalently a linear decoder) applied to the IT neural data, as opposed to requiring a nonlinear decoding scheme. In a previous study, we assessed the format of IT target match information in the context of the classic DMS task design [ 11 , 19 ] and found that while a large component was linear, a considerable nonlinear (quadratic) component existed as well.…”
Section: Resultsmentioning
confidence: 99%
“…We next consider the performance of the network after a quadratic nonlinearity g i (x) = x 2 for all neurons i [35]. In this case, both the Fisher information and mutual information are analytically intractable.…”
Section: Quadratic Nonlinearitymentioning
confidence: 99%
“…This simple architecture allowed us to analytically assess coding ability using both Fisher information [1,48,49,51], and Shannon mutual information. We evaluated the coding fidelity of both the linear representation and the nonlinear representation after a quadratic nonlinearity as a function of the distribution of synaptic weights that shape the shared variability within the representations [35]. We find that the linear stage representation's coding fidelity improves with diverse synaptic weighting, even if the Black curves denote mean responses to different stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…can be described more compactly) than the stimuli themselves. These considerations have motivated perception and neuroscience researchers to develop methods for dimensionality reduction that characterize the statistical properties of proximal stimuli, that describe the responses of neurons to those stimuli, and that specify how those responses could be decoded [3,11,12,24,28,37,43,49,45,44,50,40,31,39]. However, many of these methods are task-independent; that is, they do not explicitly consider the sensory, perceptual, or behavioral tasks for which the encoded information will be used.…”
Section: Introductionmentioning
confidence: 99%